A Novel Optical Quantal Analysis of Miniature Events Reveals Enhanced Frequency Following Amyloid β Exposure - Taylor, Henry B. C.; Tong, Rudi; Jeans, Alexander F.; Emptage, Nigel J. (Frontiers in Cellular Neuroscience, 2020)
Non-evoked miniature release of neurotransmitter is increasingly recognised as playing an important role in neural function, and is implicated in synaptic plasticity, metaplasticity, and homeostasis. Spontaneous miniature release events (minis) are usually measured electrophysiologically by recording the miniature postsynaptic currents (mEPSCs) that they evoke. However, this indirect technique can be confounded by changes within the postsynaptic neuron. Here, using the fluorescent probe SynaptopHluorin 2x, we have developed an optical method for the measurement of minis that enables direct assessment of release events. We use the technique to reveal that the frequency of minis following incubation of hippocampal neurons with Amyloid  oligomers (Ao) is increased. This contrasts with electrophysiological mEPSC data that reports a decrease in frequency under the same conditions, likely arising from changes occurring in the postsynaptic neuron. Optical quantal analysis of minis can help us to understand the important role that minis play in both normal physiology and disease and can help unmask effects obscured by postsynaptic changes.